2018
DOI: 10.1158/1538-7445.sabcs17-pd4-06
|View full text |Cite
|
Sign up to set email alerts
|

Abstract PD4-06: First-line ribociclib + letrozole in hormone receptor-positive, HER2-negative advanced breast cancer: Efficacy by baseline circulating tumor DNA alterations in MONALEESA-2

Abstract: Background: The addition of first-line ribociclib (RIB; cyclin-dependent kinase 4/6 inhibitor) to letrozole (LET) significantly improved progression-free survival (PFS) compared with placebo (PBO) + LET in patients (pts) with hormone receptor-positive (HR+), human epidermal growth factor receptor 2-negative (HER2–) advanced breast cancer (ABC) in the Phase III MONALEESA-2 study. Identifying biomarkers that predict response to treatment remains a key challenge in pts with HR+ ABC. Here we analyze results from M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…The reason for these findings remains elusive but might be due to inadequate assays to reflect protein function as well as to tumor heterogeneity and the fact that most analyses have been done with archival tissue from primary tumors. Additionally, neither ESR1 mutations nor PI3CA mutations were found to be associated with efficacy of CDK4/6 treatment [83][84][85].…”
Section: Cdk4/6 Inhibitorsmentioning
confidence: 90%
“…The reason for these findings remains elusive but might be due to inadequate assays to reflect protein function as well as to tumor heterogeneity and the fact that most analyses have been done with archival tissue from primary tumors. Additionally, neither ESR1 mutations nor PI3CA mutations were found to be associated with efficacy of CDK4/6 treatment [83][84][85].…”
Section: Cdk4/6 Inhibitorsmentioning
confidence: 90%
“…ET in HR+/HER2-MBC has been recently revolutionized by the introduction of the CDK4/6 inhibitors (i.e. palbociclib, ribociclib and abemaciclib), but a dedicated predictive biomarker is currently lacking [93][94][95][96].…”
Section: Detection Of Predictive Ctdna Alterations In the Metastatic mentioning
confidence: 99%
“…In this study, ESR1 mutations (a mutation in gene coding for the ERα) were not predictive of long term PFS improvement. Similar correlative studies performed in the MONALEESA‐2 clinical trial demonstrated that the addition of ribociclib to letrozole resulted in an improved PFS irrespective of the status of baseline ctDNA biomarkers ( RTK or ZNF703/FGFR1 alterations) …”
Section: Biomarkers Of Response To Cdk4/6 Inhibitorsmentioning
confidence: 52%
“…ER‐positivity and HER2‐non‐amplification are currently the only biomarkers used to select breast cancer patients for treatment with CDK4/6 inhibitors. Further analysis from PALOMA and MONALEESA clinical trials showed response to CDK4/6 inhibitors were not linked to a range of biomarkers from baseline samples . However sequential plasma samples analyzed from the PALOMA‐3 trial did show a decrease in PIK3CA ctDNA after 2 weeks strongly predicted for prolonged PFS with palbociclib compared to placebo .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation